Peran Influencer dan Kualitas Produk dalam Meningkatkan Keputusan Pembelian Konsumen di Era Digital - Diyah Anggitasari, Oktavia; Arqy Ahmadi, Mirzam (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Digitalization is a factor that can increase purchasing decisions because the digitalization era must follow the times. Technological developments encourage business actors to be able to adopt it for their marketing activities. While the purpose of this study is to analyze the role of influencers in increasing consumer decisions in the Digital Era and to analyze the role of product quality in increasing consumer decisions in the Digital Era. This research method uses theoretical studies and literature theories and literature review approaches while data analysis uses descriptive methods which describe findings from the literature. The results of the influence study act as opinion leaders on social media who provide recommendations to be trusted by their followers in various product categories. This influence is highly sought after by various business actors to market their products by creating several contents in the form of videos or images using these influencers to attract the interest of their followers. While product quality has a high selling value that can generate consumer interest in buying and can influence the level of consumer purchasing decisions. Factors that can influence purchasing decisions are the market, money, management, humans, motivation, materials, mechanization, modern information and process requirements.